Pengalaman Empiris Proses Sosialisasi dalam Penyelenggaraan Pilkada Jawa Timur 2018 di Kabupaten Ponorogo - Ida Royani; Ekapti Wahjuni DJ; Robby Darwis Nasution (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2018)
The socialization process in practice democracy as the selection is essential, It will have been fixed in the constitution of the institutional, During this time they have votes are missing or even to evaluate the success of the participation of determined from the about the the socialization process will be paid out starting, Institutionally in an election regional leaders the role of sub district election committee is very important, Particularly related to startegi that was undertaken in the socialization phase. The socialization process of sub-district election committee (PPK), does not success in Galag Village, Slahung sub district in Ponorogo Regency, An example of this was reflected in the amount of members of the village community ferociously who uses their voting right in 2018 year general election is now, Because has decreased compare 2 (two) election beforehand Empirical experience the socialization process in the implementation of election East Java 2018 in Ponorogo Regency.